(untitled) (Research, Society and Development, 2022)
The pandemic caused by SARS-CoV-2 (Covid-19) imposed the commercial closure and restriction of work activities in Brazil and in several countries around the world. This new reality has modified and leveraged the ready-to-eat food sales model, based on disposable packaging and utensils. A descriptive cross-sectional study was carried out, whose objective was the application of a virtual form directed to gastronomic enterprises, to study the packing and logistics of delivery of ready-to-eat foods during the pandemic period in the states of Alagoas, Minas Gerais, Pará, Pernambuco, Rio de Janeiro, and São Paulo. The delivery model by application was the most frequent as an instrument of consumption practice, using as packaging materials: plastic (65.9%), Styrofoam (48.8%); cardboard (39%) and aluminum (30.9%). These findings are worrying because, except for paper, the rest of the materials used represent strong environmental pollutants, due to the difficulty of natural decomposition and the use of costly mitigation technology.